Analysing the Social Impacts of Urbanization on Traditional and Contemporary Trading Environments: The Case of Bahrain - Noor Saleh Alalawi; Islam Elghonaimy (Alanya Üniversitesi, 2024)
The trade sector is among the top four growing sectors contributing to Bahrain’s GDP. Despite the successful impact of trade on the local economy, there is an apparent disconnect between individuals engaged in trading activities and their physical urban spaces, posing a significant threat to preserving Bahrain’s vibrant social trading culture. The research hypothesis is that effective urban design can significantly improve trading activities in the old city of Manama. Consequently, the research aims to define the role of physical urban design in influencing trade, outline the social impacts of urbanization on traditional and contemporary trading environments, and identify urban principles that affect the physical act of trade. The methodology follows a theoretical study that considers the history of urbanization and its contemporary theories, the impacts of urbanization, and the trading development impacts of urbanization on trading environments in Bahrain. An analytical study is then adopted to analyse the problem, using the “fishbone diagram”, questionnaires and photographic analysis of the area. The findings highlight the importance of utilizing outdoor space, diverse building typologies, organic circulation routes, spatial layout, interior design, landscaping, adaptable design, interaction spaces and intimate spaces within the design of traditional and contemporary trading environments. The research concludes with recommendations to sustainably revive the trading streets in Bahrain. The results provide valuable insights for stakeholders, such as Bahrain Authority for Culture and Antiquities, and those working in architecture, urban and interior design, to reignite informal social trading experiences from the past.